Pengembangan Pembelajaran Termokimia Berbasis Inkuiri Terbimbing Untuk Meningkatkan Literasi Sains Siswa - Suryati, Suryati; Permatasary, Yuni (Hydrogen: Jurnal Kependidikan Kimia, 2014)
This study is aimed in developing the thermochemical learning tools based on guided inquiry that can be used in increasing the students’ science literacy.  This learning tools consists of some steps that integrated to students worksheet, teacher’s book and lesson plan that dealing with 2013 curriculum. Inquiry learning is suitable to develop the students’ science literacy. This approach could help the teachers to increase students’ comprehension in lining their acknowledge with their daily life (students’ chemical science), and it could have more function for the students. So, one way to measure the students’ literacy by applying the inquiry steps as the learning achievement indicators. This research is in terms of 4-D design that consists of (1) defining, (2) designing, (3)developing and disseminating. The result was validated by two lecturers ( validators) that teaching chemical and four chemical teachers at senior high school, then it also tested in 40 SMAN 7 Mataram students through questionnaire. So, quantitative data then analyzed by percentage formula. Furthermore, qualitative data consists of  some ideas, suggestions in terms of the learning tools. Based on validation result from lecturers is  86%, teachers 88%. Instruments validation literacy  science result from lecturers 89%, from teachers 87%. The result from 40 students is 83%. Therefore, it can be concluded that the development learning toolsis valid to be used.